Teacher’s Reinforcement in Teaching English at the Second Year of State Islamic Senior High School 2 Kuantan Singingi - dias frahesti; harum natasha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This research was aimed to find out the teacher’s reinforcement in teaching English at the second year of State Islamic Senior High School 2 Kuantan Singingi. The subjects of this research were an English teacher and 5 students. This research was qualitative method with descriptive technique. In gathering the data, researcher distributed interview and observation to determine what components of reinforcement used by the teacher in teaching English. The result of this research showed that the English teacher at the second year of State Islamic Senior High School 2 Kuantan Singingi used verbal and non-verbal reinforcement in teaching English. For verbal reinforcement, the teacher used “reinforcement with words and reinforcement with sentence”. For non-verbal reinforcement, the teacher used “gestural reinforcement, proximity reinforcement, contact reinforcement, activity reinforcement and token reinforcement”. The reinforcement mostly often used by the teacher in teaching English is the reinforcement with words (22%), whereas the reinforcement that is rarely used by the teacher is token reinforcement (6%).